2018
DOI: 10.1515/jcim-2018-0057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complementary Spiritist Therapy on emotional status, muscle tension, and wellbeing of inpatients with HIV/AIDS: A randomized controlled trial – single–blind

Abstract: Background Complementary Spiritist Therapy includes prayer, Spiritist “passe”, fluid therapy (fluidic water or magnetized water), and spiritual education, among other therapeutic resources. The objective of this study was to evaluate the effects of Complementary Spiritist Therapy with conventional treatment on emotional status, muscle tension and wellbeing of hospitalized patients with HIV/AIDS. Methods Patients were randomly assigned into either the experimental (3 days [10 mins per day/session] of Compleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The dropout/withdrawal rate was low and similar for all groups, indicating that subjects were committed to remaining in the study. Unlike other CAM and SP trials, 13‐17,22‐27 our study used an ITT analysis, providing more solid evidence. Finally, the present study added to the current scientific literature, comparing the so‐called “spiritual healing” therapies with other interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The dropout/withdrawal rate was low and similar for all groups, indicating that subjects were committed to remaining in the study. Unlike other CAM and SP trials, 13‐17,22‐27 our study used an ITT analysis, providing more solid evidence. Finally, the present study added to the current scientific literature, comparing the so‐called “spiritual healing” therapies with other interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the scientific background of SP, the first study published on this subject was an experiment demonstrating that SP was able to inhibit bacterial growth in vitro 21 . Subsequently, some clinical trials evaluated SP, finding that participants who received SP showed reduced anxiety and depressive symptoms, negative effects and muscle tension, as well as improvements in QoL, immunological response, peripheral oxyhemoglobin saturation and well‐being 22‐27 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta terapia foi também testada como complementar em pessoas com HIV/aids em um estudo clínico randomizado controlado simples-cego, associado a outras terapias espíritas como oração, água fluidificada ou magnetizada e educação espiritual, no estado emocional, sintomas de tensão muscular e bem-estar em pacientes hospitalizados. Como resultados os autores demonstraram uma redução de efeitos negativos (p = 0,045), redução da tensão muscular (p = 0,022), aumento do bem-estar (p = 0,041) no grupo experimental combinado com o tratamento convencional, comparado ao tratamento convencional sozinho (Carneiro et al, 2018).…”
Section: Passe Espíritaunclassified
“…“External qi” therapy positively affected sympathovagal function compared to placebo, reducing the heart rate and increasing the heart rate variability [ 139 , 140 ]. These physiological mechanisms might be common to studies reporting beneficial effects of biofield practices in burnout [ 146 ], anxiety, and depression [ 147 , 148 , 149 , 150 ].…”
Section: Measuring the Effects Of Biofield Practicesmentioning
confidence: 99%